Diffusion Processes in the Vocabulary of the Ukrainian Language (for Example, Barbarisms of Mass Media Texts) (Linguostylistic Studies, 2015)
In the article the words and phrases, borrowed from other languages, are actively used in the modern Ukrainian language periodicals in a different spelling - Roman and Cyrillic, they were grouped by way of writing, analyzed the thematic unity of borrowing in the newspaper, determined their stylistic role.Characterized borrowing mainly of Anglo-American origin are caused by extralinguistic factors: the democratic processes in the society, cooperation with foreign countries, the lack of censorship and the like. There are several groups of foreign words and phrases: 1) those that are reproduced in Roman; 2) those that are written in Roman, and Cyrillic; 3) transcribed units. It was traced and described the use of neologisms in the language of periodicals, in particular, in the composition of names. Key words: barbarisms, stylistic role, language of Ukrainian periodicals, thematic focus, vocabulary diffusivity. References